Efforts to Strengthen Philosophical Foundations Islamic Education - Tata; Ajat Rukajat (Tarbiyah Departement collaboration with AMCA, 2022)
This research aims to illustrate and analyze the ideas/concepts of religious cultural development strategy in improving the character of Islam in SMPN 2 Tirtajaya, Karawang Regency. This research uses qualitative types with a case study approach. At the same time, the data collection process uses observations, interviews, and documentation of religious, cultural development strategy activities to improve Islam's character in SMPN 2 Tirtajaya, Karawang Regency. The results showed that in the framework of the religious cultural development strategy in improving the character of Islam in SMPN 2 Tirtajaya, Karawang Regency, there are 4 (four) concepts or strategies made, namely; Creation of religious atmosphere, internalization of islamic character values, islamic character model, habituation. Religious programs or behaviours are implemented through intra-curricular programs (tahfidz program, worship practice, reading al-Qur'an), co-curricular (3S culture, handshake culture, dhuha prayer, congregational prayer, tadarrus al-Quran, PHBI, istighotsah tahlil) and extracurricular (tambourine arts, yellow book studies, tartils and readings, da'wah exercises) with Religious Cultural Development Strategy, breeding, curriculum, transparency. The physical form of religious culture in this madrassa is prayer rooms and infrastructure, religious slogans and the use of Muslim clothing with managerial strategies, motivations, power.